THE STRUCTURE OF PHRASES: TYPES, SUBTYPES AND COMPLEXITY OF MIXED TYPE ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
This article provides an in-depth exploration of phrase theory, focusingon the three primary types of phrases: coordinate, subordinate, and predicative. It outlinestheir defining characteristics, subtypes, and syntactic roles within sentence structures. Additionally, the article addresses the complexities of mixed phrase types, which combineelements of multiple categories, presenting challenges for syntactic analysis. Byexamining these phenomena, the article highlights the dynamic and fluid nature oflanguage, emphasizing the importance of nuanced, context-dependent analysis. Thediscussion is aimed at enhancing understanding of sentence structure and advancingtheoretical approaches to language analysis.